Integrating epidemiology into population viability analysis: Managing the risk posed by rabies and canine distemper to the Ethiopian wolf - Haydon, D; Laurenson, M; Sillero-Zubiri, C (2002)
Infectious disease constitutes a substantial threat to the viability of endangered species. Population viability analysis (PVA) can be a useful tool for directing conservation management when decisions must be made and information is absent or incomplete. Incorporating epidemiological dynamics explicitly into a PVA framework is technically challenging, but here we make a first attempt to integrate formal stochastic models of the combined dynamics of rabies and canine distemper into a PVA of the Ethiopian wolf (Canis simensis), a critically endangered canid. In the absence of disease, populations in habitat patches of every size were remarkably stable and persistent. When rabies virus was introduced, epidemics, assumed to arise from sporadic dog-to-wolf transmission, caused extinction probabilities over 50 years to rise linearly with the force of infection from the dog reservoir and particularly steeply in smaller populations. Sensitivity analysis revealed that although the overall pattern of results was not altered fundamentally by small to moderate changes in disease-transmission rates or the way in which interpack disease transmission was modeled, results were sensitive to the process of female recruitment to male-only packs. Completely protecting wolf populations from rabies through vaccination is likely to be impractical, but the model suggested that direct vaccination of as few as 20-40% of wolves against rabies might be sufficient to eliminate the largest epidemics and therefore protect populations from the very low densities that make recovery unlikely. Additional simulations suggested that the affect of periodic epidemics of canine distemper virus on wolf population persistence was likely to be slight, even when modeled together with rabies. From a management perspective, our results suggest that conservation action to protect even the smallest populations of Ethiopian wolves from rabies is both worthwhile and urgent.